Sistem Monitoring Dan Pengendalian Kinerja Dosen Pada Proses Perkuliahan Berbasis Radio Frequency Identification (RFID) Di Lingkungan Universitas Kanjuruhan Malang - Mohamad Sulhan (IC-ITECHS, 2014)
Radio Frequency Identification application (RFID) has been developed to date. One application RFID. One of RFID applications developed here is a system of monitoring and controlling the lecturers performance in the lecture. In the recording system lecturers are present at each college requires a signature on the list of attendance or presence at every lecture. This situation allows and the chance of fraud in attendance lecturers where lecturers not teaching, but still have the attendance of teaching. Thus it is important to establish a monitoring system that automatically controlled and computerized by RFID-based, so it can provide accurate information, especially in Kanjuruhan University of Malang. From research conducted found that the RFID reader can detect and read the RFID ID card, and assisted with the software as an interface can read the records in the database and display monitor in accordance with the lecturer's name stored in the database. And any data that is detected will be stored in a database so easy to be viewed / monitored by the authorities